Wasps of the subfamily Bembicinae (Hymenoptera, Crabronidae) in the collection of the Institute of Zoology, Ministry of Science and Education of the Republic of Azerbaijan - Mammadov, Aydin A.; Maharramov, Mahir M. (Acta Biologica Sibirica, 2024)
The collection materials of Crabronidae wasps in Institute of Zoology (Baku) presented at the following 16 species from seven Bembicinae genera. Sixteen species are recorded from Azerbaijan, two – from Russia, and six species from Iran. Gorytes laticinctus Lepeletier, 1832 is newly recorded from Caucasus and Gorytes procrustes Handlirsch, 1888 from Azerbaijan.